AMAP Assessment 2015: Temporal Trends in Persistent Organic Pollutants in the Arctic - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2016)
A fully referenced, comprehensive scientific and technical report presenting the 2015 AMAP assessment of temporal trends of persistent organic pollutants (POPs) in the Arctic; prepared by the Arctic Monitoring and Assessment Programme (AMAP).